Pengaruh Permainan Lipat Kertas (Origami ) Terhadap Perkembangan Motorik Halus Anak Pra Sekolah Usia 4-5 Tahun di TK Muslimat - Ajeng Indah Prastika; Anik Sri Purwanti; Rosyidah Alfitri (Lembaga Pengembangan Kinerja Dosen, 2025)
Fine motor skills are one of the crucial dimensions in child development, playing a significant role in supporting various basic daily activities such as writing, drawing, and using cutting tools (e.g., scissors). However, various data indicate that a considerable number of preschool children experience delays in developing this aspect. This study aims to examine the effect of paper folding activities (origami) on enhancing fine motor skills in preschool children aged 4–5 years at TK Muslimat NU 11 Malang. The study employed a pre-experimental design using a one-group pretest-posttest model. A total of 20 participants were selected through purposive sampling based on predetermined inclusion and exclusion criteria. The data collection instrument used was an observation sheet developed based on fine motor skill development indicators. The analysis using the Wilcoxon test revealed a statistically significant difference after the origami game intervention was applied (p = 0.000 < 0.05). Prior to the intervention, the majority of participants were in the